A qualitative study exploring the experiences of Muslim women in the South African workplace - Nuraan Agherdien (SA Journal of Human Resource Management)
Orientation: More Muslim women are entering the labour market, and this requires an understanding of the cultural and social contexts as there may be challenges inhibiting their growth and advancement.